The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/6659775
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry and Biological Activities of Poria

Abstract: Poria is a common Traditional Chinese Medicine in clinic. In recent years, the chemical and pharmacological studies of Poria have made great progress, triterpenes and polysaccharides have been isolated, and various types of compounds containing lipids, octanoic acids, fatty acids, and trace elements have been found. In this paper, we reviewed the literature, summarized the main compound types, and reviewed in detail their pharmacological effects in antitumor, immunomodulatory, effects on kidney, hepatoprotecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Ganoderma lucidum and Poria cocos are two well-known medicinal basidiomycetes. Based on the phytochemical reports, more than 270 secondary metabolites have been reported to be isolated from Ganoderma lucidum [ 60 , 61 , 62 ]; more than 140 terpenoids and more than 20 steroids have been identified in Poria cocos [ 63 , 64 ]. As reviewed by Habtemariam [ 1 ] and described in the Section 1 , the small-molecule compounds identified from D. indusiata mainly include a few terpenoids and alkaloids.…”
Section: Discussionmentioning
confidence: 99%
“…Ganoderma lucidum and Poria cocos are two well-known medicinal basidiomycetes. Based on the phytochemical reports, more than 270 secondary metabolites have been reported to be isolated from Ganoderma lucidum [ 60 , 61 , 62 ]; more than 140 terpenoids and more than 20 steroids have been identified in Poria cocos [ 63 , 64 ]. As reviewed by Habtemariam [ 1 ] and described in the Section 1 , the small-molecule compounds identified from D. indusiata mainly include a few terpenoids and alkaloids.…”
Section: Discussionmentioning
confidence: 99%
“…A limited amount of research on the pharmacological activity, underlying molecular mechanisms and other new biological effects of PA warrants further investigation ( 8 ). Investigators use different methods including experimental animals ( in vivo ), tissue and cell cultures ( in vitro ) in order to investigate novel therapies of human diseases ( 94 ).…”
Section: Discussionmentioning
confidence: 99%
“…Its sclerotium, known as fu-ling or hoelen, has been widely used as a health food and in traditional Chinese medicine with pharmacological properties, including sedative, diuretic, and tonic effects (5)(6)(7). Overall, >160 terpenoids have been identified in Poria cocos (8). As an important bioactive terpenoid, PA has been reported to exhibit numerous pharmacological effects, such as cytotoxic (9), anti-inflammatory (10), antihyperglycemic (11), antibacterial and antiviral (12), sedative-hypnotic (13) and anti-ischemia/reperfusion (14) effects.…”
Section: Introductionmentioning
confidence: 99%
“…Wolf. Lu et al(2021 ) have been reported to involve the modulation of redox signaling including the inhibition of pro-inflammatory nuclear factor kappa B signaling and its target genes as well as the activation of antioxidative nuclear factor-erythroid-2-related factor 2 signaling and its downstream target gene in TGF-β1. Alisol B (acetate), Alisol C (monoacetate) account for 65% of chemical compounds identified from Alisma Orientale (Sam.)…”
Section: Discussionmentioning
confidence: 99%